2021
DOI: 10.3167/latiss.2021.140103
|View full text |Cite
|
Sign up to set email alerts
|

Precarity and dehumanisation in higher education

Abstract: The increased reliance of universities on a pool of highly skilled but poorly paid casualised academic labour for teaching and research has emerged as a defining feature of higher education provision under neoliberal New Public Management. Based on seventeen visual timeline interviews with academics in the North East of England, this article augments and extends existing studies of precarity through a framing of dehumanisation and humanisation. Specifically, we suggest that casualisation is dehumanising in fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Preferences for (e.g., Loh, 2004) and circumstances which require (e.g., Langan & Morton, 2009; Mapes, 2019) seeking of information through informal, social sources have been noted. Yet, for some CAS, even these sources were seen as unavailable (e.g., Mason & Megoran, 2021) or challenging to identify (Willson & Julien, 2020), creating more isolation from important workplace information. Additionally, direct discussion of official policies and documents involved in interactions between CAS and higher education institutions is rare, and detailed information from institutions about their contract appointments is often lacking (Brownlee, 2015).…”
Section: Preliminary Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Preferences for (e.g., Loh, 2004) and circumstances which require (e.g., Langan & Morton, 2009; Mapes, 2019) seeking of information through informal, social sources have been noted. Yet, for some CAS, even these sources were seen as unavailable (e.g., Mason & Megoran, 2021) or challenging to identify (Willson & Julien, 2020), creating more isolation from important workplace information. Additionally, direct discussion of official policies and documents involved in interactions between CAS and higher education institutions is rare, and detailed information from institutions about their contract appointments is often lacking (Brownlee, 2015).…”
Section: Preliminary Findingsmentioning
confidence: 99%
“…In the literature reviewed, several documents suggest CAS face a variety of temporal realities that are often incongruous with the traditional duties of academics. A lack of time, both for teaching preparation and research activities (e.g., Ivancheva, 2015), an inability to plan for or even anticipate the future, on personal, professional, and financial levels (e.g., Lopes & Dewar, 2014; Mason & Megoran, 2021), and fears around running out of time and falling into a perpetual cycle of part‐time roles (Roy et al, 2021), have been suggested. Furthermore, pressures of time have been seen as particularly impactful for CAS with disabilities (e.g., Butler‐Rees & Robinson, 2020).…”
Section: Preliminary Findingsmentioning
confidence: 99%
“…However, the majority of the teaching workforce were estimated to be casually employed prior to COVID-19 (Evans et al 2019). Increasing casual and precarious employment in higher education has been noted internationally as a trend and concern (Mason and Megoran 2021;Leathwood and Read 2022). Casual or sessional teaching staff have little power over students or to effect change in teaching or learning practices.…”
Section: Playing the Set Game: How Teachers View The Impact Of Studen...mentioning
confidence: 99%
“…Similarly, access to support that we trust or have built relationships with might be our first priority (e.g., counsellors, shared-interest, community, and advocacy groups). Or we -as for the majority [42] -of course have freedom of choice to simply put stability in secure employ ahead of precarious alternatives that can negatively impact wellbeing and job satisfaction [43,44], restrict our wider lives, and can be infantilising and dehumanising [45].…”
Section: Some Remarks On Mobility Stability and Fulfilmentmentioning
confidence: 99%